2021
DOI: 10.1007/s10856-021-06519-5
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and evaluation of porous and conductive nanofibrous scaffolds for nerve tissue engineering

Abstract: Peripheral nerve repair is still one of the major clinical challenges which has received a great deal of attention. Nerve tissue engineering is a novel treatment approach that provides a permissive environment for neural cells to overcome the constraints of repair. Conductivity and interconnected porosity are two required characteristics for a scaffold to be effective in nerve regeneration. In this study, we aimed to fabricate a conductive scaffold with controlled porosity using polycaprolactone (PCL) and chit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The electrical conductivity properties of the polymer scaffolds were measured by the two-probe method [ 49 ], using a resistance meter (TRMS Fluke 87-V). The samples were cut into 13 mm 2 -sized pieces.…”
Section: Methodsmentioning
confidence: 99%
“…The electrical conductivity properties of the polymer scaffolds were measured by the two-probe method [ 49 ], using a resistance meter (TRMS Fluke 87-V). The samples were cut into 13 mm 2 -sized pieces.…”
Section: Methodsmentioning
confidence: 99%
“…The addition of gold nanoparticles and sacrificial fiber (40% of polyethylene oxide) helped to achieve a desirable interconnected porosity, formed a spherical shape of gold nanoparticles with narrow particle size distribution (126 ± 20 nm), and improved surface hydrophilicity (75–80%) of the scaffold. The results of FE-SEM and MTT assay showed that the scaffold had no cytotoxic effect on stem cells and can support spindle-shaped morphology similar to mature Schwann cell cultures with some proliferation of cells [ 149 ]. Another research group demonstrated the fabrication of poly (L-lactic acid) (PLLA)/chitosan-based scaffold by using a liquid–liquid phase separation technique.…”
Section: Cardiac and Nervous Tissuesmentioning
confidence: 99%
“…The resultant 3D rGO/PCL/Mel hybrid conduit exhibits a lightweight density of (144.3 ± 1.27) mg/cm 3 and the highest reported porosity of (98.5 ± 0.24)% (Figure S9), surpassing that of other natural or synthetic conduits (Fig. 3k) [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] . This remarkable achievement is attributed to the precise regulation of the rGO conduit's microstructural features, from the microscale to macroscopic dimension, by controlling the GO ink's owing state and fabrication parameters such as freeze-casting temperature.…”
Section: The Structural Characterization Of 3d Rgo/pcl/mel Conduitmentioning
confidence: 99%